EXPERIMENTAL INVESTIGATION OF THE EFFECT OF METASOMATISM BY CARBONATIC MELT ON THE COMPOSITION AND STRUCTURE OF THE DEEP MANTLE - Gasparik T.; Litvin Y.A. (My University, 2002)
The compositions of various transition-zone and lower-mantle phases and coexisting carbonatic melts were determined by exploratory melting experiments in chemically complex CO2-bearing systems at 20–24.5 GPa and 1600–2000 °C. The melts are highly ultramafic, enriched in K, Na, Ca, Fe, and Mg, and depleted in Al and Si. Melting experiments were also carried out with the compositions on the join Mg2SiO4–Na2CO3 at 3.7 GPa and 1200–1600 °C. The solidus assemblage of MgCO3 and Na2MgSiO4 melts incongruently to produce forsterite and Na-rich melt. The new results and other recent studies in CO2-bearing systems suggest that carbonatic melt could be present, either transiently or permanently, in the whole Earth's upper mantle and at least the uppermost lower mantle. Carbonate-melt metasomatism is recognized as a process that could have a major effect on the composition and structure of the deep mantle, and thus play an important role in its evolution. Due to the unique properties of the carbonatic melt, its circulation in an otherwise static mantle could be a more efficient process than the solid-state convection for maintaining equilibrium in most of the mantle not involved directly in plate tectonics.